Climate Warming Facilitates Seed Germination in Native but Not Invasive Solidago canadensis Populations - Zhou, Xiao-Hui; He, Wei-Ming (Frontiers in Ecology and Evolution, 2020)
Plant performance is commonly temperature-dependent so that this performance could vary with climate warming. Seeds are among the most important propagules of plants, and seed traits strongly influence plant invasion success. Therefore, understanding seed traits under climate warming is useful for predicting invasion risks. To this end, we conducted a warming experiment with an infrared radiator and examined the effects of 5-year warming (approximately 2ºC above ambient) on the seed quality and subsequent germination of Solidago canadensis from North America, where it is native (24 native populations), and from China, where it is invasive (29 invasive populations). Temperature regimes (i.e., ambient versus warming) interacted with population sources (i.e., native versus invasive) to significantly influence seed germination, but not thousand-seed mass. Warming significantly advanced the seed germination timing of native S. canadensis populations and increased their seed germination rate; warming did not influence the germination timing but decreased the germination rate of invasive S. canadensis populations. Across two temperature regimes combined, 24 native S. canadensis populations had smaller seeds, later germination timing, and lower germination rate than 29 invasive S. canadensis populations. These findings suggest that climate warming as an environmental cue couldmay facilitate the seed germination of native but not invasive populations. Our data also highlight that invasive populations might be more successful than native populations due to better seed quality and faster and higher seed germination.